Follow-up in colon cancer: How and until when? Pray. - Sarroca, Carlos; Della Valle, Adriana; Leites, Alejandro; Denis, María; Alonso, Juan Carlos; Fresco, Rodrigo; Simonet, Fernando; Rodríguez, Alejandro (Cirugía del Uruguay, 2005)
lntroduction: There is no consensus as to the manner of implementing follow-up in the case of patients who have undergone curative surgery for colonic cancer (CC). Oftentimes it is exhaustive, entai/s unnecessary and excessive monitoring and considerable out/ay in health procedures. The idea behind this study is to set up guidelines for the tollow-up of patients who have undergone surgery for co/onic cancer (CC), by drawing up a protoco/ based o scientific evidence and the experience of our working group.